2014
DOI: 10.3892/or.2014.3325
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinase A is a possible target of OSU-03012 to destabilize MYC family proteins

Abstract: OSU-03012, a 3-phosphoinositide-dependent kinase-1 (PDK1) inhibitor, destabilizes MYCN and MYC proteins in neuroblastoma cells. However, AKT phosphorylation is barely detectable in neuroblastoma cells under normal culture conditions whether treated with OSU-03012 or not. This observation suggests that PDK1 is not the main target of OSU-03012 to destabilize MYC and MYCN in neuroblastoma cells. In the present study, we explored one of the possible mechanisms by which OSU-03012 destabilizes MYC and MYCN. Since Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…We confirmed the on‐target activity of I‐BET151 against BRD4, demonstrating the transcriptional repression of multiple canonical BRD4 targets previously validated in different cancers . We also confirmed AURKA kinase inhibition by alisertib and concomitant MYC repression, consistent with prior studies . Our work does not preclude other biological impacts of alisertib and I‐BET151 on ES biology; in fact, we do confirm that BRD4 inhibition does impair EWS‐FLI1‐mediated transcriptional activation as shown by I‐BET151's repression of NR0B1, consistent with recent data .…”
Section: Discussionsupporting
confidence: 89%
“…We confirmed the on‐target activity of I‐BET151 against BRD4, demonstrating the transcriptional repression of multiple canonical BRD4 targets previously validated in different cancers . We also confirmed AURKA kinase inhibition by alisertib and concomitant MYC repression, consistent with prior studies . Our work does not preclude other biological impacts of alisertib and I‐BET151 on ES biology; in fact, we do confirm that BRD4 inhibition does impair EWS‐FLI1‐mediated transcriptional activation as shown by I‐BET151's repression of NR0B1, consistent with recent data .…”
Section: Discussionsupporting
confidence: 89%
“…Despite intense investigations, no effective strategies exist to target C-MYC. C-MYC upregulates the expression of AURKA [41], while AURKA activity protects C-MYC from degradation [42]. AURKA signals through C-MYC to induce telomerase, supporting tumor immortalization [43].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that AURKA can regulate transcription of c-MYC through the activation of b-catenin (Dar et al, 2009). Recent studies have shown that inhibition of AURKA can regulate phosphorylation and stability of MYC, suggesting targeting AURKA-MYC axis by AURKA inhibitors as a novel potentially effective therapeutic approach (Dauch et al, 2016;Richards et al, 2016;Silva et al, 2014). We investigated whether eIF4E and its downstream effector, c-MYC, mediate the function of AURKA and CDDP resistance.…”
Section: Discussionmentioning
confidence: 99%